KSOCIO-ECONOMIC SIGNIFICANCE OF THE DEVELOPMENT OF THE AGRI-FOOD MARKET (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The article analyzes the socio-economic significance of the development of the agri-food market, its interrelation with food security, regional development, employment, and social stability from a scientific and theoretical perspective. The study shows that structural changes in the agricultural sector and the state’s regulatory policies play a key role in ensuring market resilience. The author’s analysis identifies that institutional and structural limitations in Azerbaijan’s agri-food market persist: weak development of agricultural cooperatives, uneven distribution of the processing industry, incomplete logistics infrastructure, and targeting issues in state support mechanisms limit efficiency. Comparative analysis of international experience shows that the competitiveness of agricultural markets in developed countries is ensured by strong cooperative models, innovative processing technologies, digital management systems, and institutional foundations of public-private partnerships. The article emphasizes that for sustainable development of Azerbaijan’s agri-food market, integration of the production–processing–logistics chain, expansion of digitalization processes, promotion of local brands, and stimulation of export-oriented production are necessary. Furthermore, enhancing the knowledge and skills of market participants, along with the application of modern marketing and trade strategies, plays a significant role in increasing competitiveness. Targeted and transparent implementation of subsidies and investment incentives by the state improves efficiency. Regional market development requires promoting local production and improving logistics infrastructure. At the same time, strengthening the activities of agricultural research institutes and innovation centers facilitates technology transfer and productivity enhancement. In conclusion, modernization of the agrifood market is a strategic direction that ensures not only economic efficiency but also social welfare, food security, and balanced regional development. Thus, the comprehensive and sustainable development of the agri-food market directly contributes to the growth of both economic and social indicators.
Keywords: Agri-food market, food security, agriculture, state policy, socio-economic development, logistics and processing, international experience, cooperative model, competitiveness, innovative mechanisms.